Umbilical vein catheterisation for the family physician working in primary health care - Indiran Govender; Henry I. Okonta; Olukayode Adeleke; Selvandran Rangiah (South African Family Practice)
This is part of a series of articles on vascular access in emergencies. The other two articles were on intra osseous lines and central venous lines. These are critical lifesaving emergency skills for the primary care professional. In this article, we will provide an overview of umbilical vein catheterisation highlighting its importance, the indications, contraindications, techniques, complications and nursing considerations. By familiarising healthcare providers with this procedure, we hope to enhance their knowledge and skills, ultimately leading to improved outcomes in the neonatal population.